Effect of Omega-3 Fatty Acid Supplementation on Platelet Aggregability and Platelet Produced Thromboxane - Salonen, Riitta; Nikkari, Tapio; Seppänen, Kari; Venäläinen, Juha M; Ihanainen, Merja; Rissanen, Viljo; Rauramaa, Rainer; Salonen, Jukka T (Thrombosis and Haemostasis, 1987)
We investigated the sustained effect of 12-week supplementation of 2.880 g/day of omega-3 fatty acids on platelet aggregability, platelet produced thromboxane B2 concentration and serum fatty acid composition in a double-blind controlled trial in 44 healthy mildly overweight eastern Finnish men recruited from a representative population sample. The supplementation was discontinued seven days before the biochemical measurements. Body weight, alcohol consumption and dietary composition remained constant during the study. Even though the percentage of eicosapentaenoic acid (20:5ω3) in total serum lipids increased by 37% (p <0.01) and that of dihomo-gamma-linolenic acid (20:3ω6) decreased by 18% (p <0.01) more in the omega-3 supplemented than placebo group during supplementation, there were no significant differences in the changes in either the ADP induced platelet aggregation or in vitro platelet produced thromboxane B2 concentration between the groups. These data suggest that omega-3 fatty acids have no detectable sustained effect either on ADP induced platelet aggregation or on thromboxane produced by the platelets in vitro.
Keywords: ω-3 fatty acids; Fish oil; Thrombocyte aggregation; Prostaglandins